The Utilization of ZEP Quiz in an EFL Inclusive Reading Classroom: A Focus of Teacher’s Perception - Alfina Salsabila, Hawa; Rahmah Fithriani (Universitas Cokroaminoto Palopo, 2026)
Rapid technological advancement has encouraged the integration of gamification in English language teaching to enhance student engagement. However, the effectiveness of technological tools largely depends on teachers’ perceptions and instructional decisions, particularly in inclusive learning contexts. This study aims to explore teachers’ perceptions of the use of ZEP Quiz in an inclusive English reading classroom, particularly regarding its influence on students’ motivation to develop reading skills and the challenges teachers face during its implementation. Employing a qualitative case study design, the study involved an English teacher and a shadow teacher teaching ninth-grade students in an inclusive classroom with a slow learner. Data were collected through semi-structured interviews and documentation and were analyzed thematically using the ARCS motivational framework (Attention, Relevance, Confidence, and Satisfaction). The findings indicate that, from the English teacher’s perspective, ZEP Quiz enhances students’ attention through interactive features, supports reading comprehension when combined with structured guidance, increases students’ confidence in answering reading questions, and fosters learning satisfaction through engaging and competitive elements. In contrast, the shadow teacher perceived that while ZEP Quiz could stimulate motivation and provide reading exposure for the slow learner, its effectiveness in developing independent comprehension remained limited without continuous scaffolding, emotional support, and peer assistance. Several challenges were also identified, including limited device availability, restrictive school policies regarding gadget use, unstable internet connectivity, and the need for ongoing pedagogical adaptation to accommodate diverse learner characteristics in inclusive settings.